PROSES PRODUKSI KOMPONEN DUDUKAN WINCH KENDARAAN KHUSUS TAKTIS MAUNG 4X4 - Sitinjak, Heryanto; Supardi, Nurul Iman; Bismantolo, Putra (Rekayasa Mekanika: Jurnal Ilmiah Teknik Mesin, 2023)
In accelerating production, the manufacturing process uses modern equipment such as machines and implements a structured program to carry out production. This study aims to determine the process of making winch mount components for Maung 4x4 special tactical vehicles. The manufacturing process begins with designing the product, determining the specifications of the material from which the product is made. After that, the raw material is modified through a manufacturing process to be formed into the required parts. To speed up and simplify the production process, a CNC (Computer Numerical Control) machine is used which works automatically according to the program made. To produce a desired product, of course, must go through several stages. In production the manufacturing process requires machining stages. This is because the desired product cannot be produced through only one machining process. Manufacturing steps, namely, making component designs, material verification (material verification) cutting processes, bending processes, and welding processes.